Peran Suami dalam Deteksi Dini Tanda Bahaya Kehamilan sebagai Upaya Pencegahan Kegawatdaruratan pada Ibu Hamil: The Role of Husbands in the Early Detection of Pregnancy Danger Signs as an Effort to Prevent Obstetric Emergencies in Pregnant Women - Sinulingga, Yeni Friska; Sihaloho, Endang; Rizki, Hudeni; Daulay, Evlindari Sentani (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Obstetric emergencies remain a leading cause of maternal mortality in Indonesia, most of which are preventable through early detection of pregnancy danger signs. One of the key factors in the success of early detection is the involvement of family members, particularly the husband as the primary support for pregnant women. However, the involvement of husbands in this aspect remains limited and suboptimal. This study aims to explore the role of husbands in the early detection of pregnancy danger signs as a preventive effort against obstetric emergencies in pregnant women. This research employed a descriptive qualitative approach through in-depth interviews with six husbands of pregnant women undergoing antenatal care at Sunggal Public Health Center, Medan, in January 2025. The study population consisted of husbands of pregnant women who met the inclusion criteria. Data were collected using a semi-structured interview guide, recorded, transcribed, and analyzed using thematic analysis. The main variable in this study was the role of husbands in identifying danger signs during pregnancy, with interviews serving as the primary instrument. Data validity was ensured through source triangulation and member checking. The results revealed three main themes: husbands' knowledge and awareness of danger signs, forms of involvement in preventing emergencies, and barriers to participation. Most informants recognized prominent danger signs such as bleeding and severe pain but were unaware of symptoms like preeclampsia or premature rupture of membranes. Forms of support included accompanying their wives to health facilities, assisting with household chores, and paying attention to complaints. The main obstacles included limited time, lack of direct information from healthcare providers, and cultural influences that consider pregnancy a woman's domain. In conclusion, although some husbands demonstrated concern, their involvement in early detection of pregnancy danger signs needs to be strengthened. Recommendations are directed at communities and healthcare providers to actively engage husbands in pregnancy education programs, including through interactive media, father classes, and community-based approaches, in order to significantly reduce the incidence of obstetric emergencies in pregnant women.